Damage-regulated autophagy modulator 1 in oral inflammation and infection - Memmert, Svenja; Nogueira, A. V.B. [UNESP]; Damanaki, A.; Nokhbehsaim, M.; Eick, S.; Divnic-Resnik, T.; Spahr, A.; Rath-Deschner, B.; Till, A.; Götz, W.; Cirelli, J. A. [UNESP]; Jäger, A.; et al. (Springer Nature, 2018)
Objectives: Damage-regulated autophagy modulator (DRAM) 1 is a p53 target gene with possible involvement in oral inflammation and infection. This study sought to examine the presence and regulation of DRAM1 in periodontal diseases. Material and methods: In vitro, human periodontal ligament fibroblasts were exposed to interleukin (IL)-1β and Fusobacterium nucleatum for up to 2 days. The DRAM1 synthesis and its regulation were analyzed by real-time PCR, immunocytochemistry, and ELISA. Expressions of other autophagy-associated genes were also studied by real-time PCR. In vivo, synthesis of DRAM1 in gingival biopsies from rats and patients with and without periodontal disease was examined by real-time PCR and immunohistochemistry. For statistics, ANOVA and post-hoc tests were applied (p < 0.05). Results: In vitro, DRAM1 was significantly upregulated by IL-1β and F. nucleatum over 2 days and a wide range of concentrations. Additionally, increased DRAM1 protein levels in response to both stimulants were observed. Autophagy-associated genes ATG3, BAK1, HDAC6, and IRGM were also upregulated under inflammatory or infectious conditions. In vivo, the DRAM1 gene expression was significantly enhanced in rat gingival biopsies with induced periodontitis as compared to control. Significantly increased DRAM1 levels were also detected in human gingival biopsies from sites of periodontitis as compared to healthy sites. Conclusion: Our data provide novel evidence that DRAM1 is increased under inflammatory and infectious conditions in periodontal cells and tissues, suggesting a pivotal role of DRAM1 in oral inflammation and infection. Clinical relevance: DRAM1 might be a promising target in future diagnostic and treatment strategies for periodontitis.
Keywords: Autophagy; Damage-regulated autophagy modulator; Fusobacterium nucleatum; Interleukin-1β; Periodontal ligament; Periodontitis